Immunohistochemical Study of Tissue Expression of Trophoblast Cell Surface Antigen 2 (TROP2) Protein in Prostatic Carcinoma and Benign Hyperplasia - Abdel-Hafeez, Mennat Allah Mohammed; Hammam, Makram Mohamed; El-Okda, Mohamed Osama Ibrahim; Farouk, Sahar; El-Kherbetawy, Mohammed Kamal (Asian Pacific Journal of Cancer Biology, 2026)
Background: Prostate cancer is the second most common malignancy affecting males. TROP2 is a cell surface marker of embryonic stem cells that has been implicated in development of many cancers. Objective: This study aimed to investigate the immunohistochemical expression of TROP2 Protein in PCa and BPH tissues and explore TROP2 association with the histopathological parameters of PCa. Materials and Methods: a cross-sectional analytical study was conducted in the pathology laboratory of Suez Canal University Hospital on thirty PCa and fifteen BPH specimens (n=45). Sample was collected from the archived blocks of BPH and prostatic carcinoma. TROP2 expression was assessed using immunohistochemistry. Results: TROP2 showed positive membranous staining in prostatic epithelial cells of 100% of PCa & in eleven out of fifteen BPH specimens and the difference between the two groups was statistically significant (p-value >0.001). Moreover, high TROP2 expression was found in nineteen PCa and in only four BPH specimens and the difference between the two groups regarding TROP2 staining intensity was also statistically significant (p-value= 0.005). TROP2 showed positive expression in 100% of specimens showing positive perineural invasion and a statistically significant association was found between both TROP2 staining intensity and perineural invasion (p-value >0.05). In addition, TROP2 showed statistically significant validity in discriminating between PCa and BPH (p-value <0.001). Conclusions: TROP2 is a sensitive prostatic immunohistochemical marker and its expression in PCa is higher than that in BPH. TROP2 is associated with poor prognostic factors of PCa as perineural invasion.